1999
DOI: 10.1086/307786
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of the Galactic Bar Implied by Gas Kinematics in the Inner Milky Way

Abstract: Longitude-velocity (ℓ−V ) diagrams of H I and CO gas in the inner Milky Way have long been known to be inconsistent with circular motion in an axisymmetric potential. Several lines of evidence suggest that the Galaxy is barred, and gas flow in a barred potential could be consistent with the observed "forbidden" velocities and other features in the data. We compare the H I observations to ℓ − V diagrams synthesized from 2-D fluid dynamical simulations of gas flows in a family of barred potentials. The gas flow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
157
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(179 citation statements)
references
References 54 publications
21
157
1
Order By: Relevance
“…Mass and orientation of the bar Several studies suggest that the mass of the COBE/DIRBE bar is in the range 0.98-2×10 10 M (Weiner & Sellwood 1999;Dwek et al 1995;Matsumoto et al 1982;Zhao 1996). Given that the bar is formed from the bulge, we assume the mass of the bar is in the range 9.8 × 10 9 − 1.4 × 10 10 M .…”
Section: Galactic Bar Parametersmentioning
confidence: 99%
“…Mass and orientation of the bar Several studies suggest that the mass of the COBE/DIRBE bar is in the range 0.98-2×10 10 M (Weiner & Sellwood 1999;Dwek et al 1995;Matsumoto et al 1982;Zhao 1996). Given that the bar is formed from the bulge, we assume the mass of the bar is in the range 9.8 × 10 9 − 1.4 × 10 10 M .…”
Section: Galactic Bar Parametersmentioning
confidence: 99%
“…An examination of the Galactic-longitude-velocity diagrams of CO emission (Dame et al 2001), H i (see Fig. 1 in Weiner & Sellwood 1999), Galactic planetary nebulae (Durand et al 1998) and OH/IR and SiO-maser stars (Habing et al 2006) shows that the observed velocities of V383 Sco and V381 Sco fall into regions close to the Galactic centre with very high velocities. The kinematics of the gas in these regions is inconsistent with purely circular motion (Dame et al 2001;Weiner & Sellwood 1999, and references therein).…”
Section: High-resolution Spectramentioning
confidence: 99%
“…(Pichardo et al 2003 References. ( * ) Weiner & Sellwood (1999), Fux (1999), Ibata & Gilmore (1995), Englmaier & Gerhard (1999). We emphasize that the absolute PM presented here is based on direct observations of background galaxies, used to define the absolute reference frame.…”
Section: Observations Data Reduction Proper Motionsmentioning
confidence: 99%